Incidence and prevalence of celiac disease and dermatitis herpetiformis in the UK over two decades: population-based study - West, Joe; Fleming, Kate M.; Tata, Laila J.; Card, Timothy R.; Crooks, Colin J. (Nature Publishing Group, 2014)
OBJECTIVES: Few studies have quantified the incidence and prevalence of celiac disease (CD) and dermatitis herpetiformis (DH) nationally and regionally by time and age groups. Understanding this epidemiology is crucial for hypothesizing about causes and quantifying the burden of disease. METHODS: Patients with CD or DH were identified in the Clinical Practice Research Datalink between 1990 and 2011. Incidence rates and prevalence were calculated by age, sex, year, and region of residence. Incidence rate ratios (IRR) adjusted for age, sex, and region were calculated with Poisson regression. RESULTS: A total of 9,087 incident cases of CD and 809 incident cases of DH were identified. Between 1990 and 2011, the incidence rate of CD increased from 5.2 per 100,000 (95% confidence interval (CI), 3.8-6.8) to 19.1 per 100,000 person-years (95% CI, 17.8-20.5; IRR, 3.6; 95% CI, 2.7-4.8). The incidence of DH decreased over the same time period from 1.8 per 100,000 to 0.8 per 100,000 person-years (average annual IRR, 0.96; 95% CI, 0.94-0.97). The absolute incidence of CD per 100,000 person-years ranged from 22.3 in Northern Ireland to 10 in London. There were large regional variations in prevalence for CD but not DH. CONCLUSIONS: We found a fourfold increase in the incidence of CD in the United Kingdom over 22 years, with large regional variations in prevalence. This contrasted with a 4% annual decrease in the incidence of DH, with minimal regional variations in prevalence. These contrasts could reflect differences in diagnosis between CD (serological diagnosis and case finding) and DH (symptomatic presentation) or the possibility that diagnosing and treating CD prevents the development of DH.